Teaching the adolescent brain - D'Arcangelo, Marcia; Sheets, Dana; Association for Supervision and Curriculum Development (Alexandria, VA : ASCD, 2006)
These programs looks at the changes that occur in the developing brains of healthy teens and explores what these cognitive and emotional changes might imply for classroom practice and intended to be used with students and explains why the teen years can be so challenging
program 1. Almost adults (28 min.) -- program 2. The engaged teen (29 min.) -- program 3. The reflective teen (30 min.) -- program 4. Know your brain...know yourself (12 min.)
Title from title screen
Editor, Melanie Maholick ; camera, Dominic Desantis ; sound, Robert Silverthorne ; lighting, Donny Aros
Keywords: Teaching; Effective teaching; Learning -- Physiological aspects; Brain